Split Payment as a Method of Consumer Payment in Online Buying and Selling Practices Is Reviewed From the Principle of Legal Certainty - Wahyuni, Sri (Universitas Airlangga, 2024)
Current technological advances have led to the development of payment methods in online buying and selling practices. Usually the payment method is made via cash and non-cash; one of the current payment methods is known as the split payment method. Split payment is a payment made using more than one payment method to complete the entire transaction. There is a case where a consumer buys goods online by paying using split payment and the consumer will be given cash back when using split payment. However, the goods that have been purchased do not reach the consumer. The consumer and the shop agreed to ask for compensation from the market place, which is a meeting place for online buyers and sellers. Based on this case, the author is interested in researching the problem of how to complete online buying and selling transactions using split payments. This research uses normative legal research methods with a statutory approach. The results of this research show that it is important to have special regulations regarding the definition and validity of split payment methods for online buying and selling transactions in order to provide guarantees, justice and consumer security in order to realize the principle of legal certainty.